Peran Notaris Dalam Proses Pembuatan Akta Pendirian Perseroan Terbatas - Siti Fauziah Dian Novita Sari (Lex Renaissance, 2018)
This study aims to examine the role of a notary in the process of drafting a Deed of Establishment of a Limited Liability Company (PT) and the authority of a public notary in providing legal counseling to the applicant. This study uses a juridical-empirical method by exploring information obtained from interviews and data from literature studies. The analytical method used is qualitative and then presented in the form of descriptive scientific work. The results concluded that the notary's role was to confirm the will of the founders, and to provide legal counsel in accordance with Law No. 40 of 2007 on Limited Liability Companies to be formulated in the Deed of Establishment of the Limited Liability Company, the notary also has the role as the attorney for founders to obtain the legal entity status from the Deed of Establishment until its announcement of the Company in the Official Gazette of the Republic of Indonesia. The responsibility of the public notary in the Deed of Establishment is only limited to the formal truth conveyed by the parties but must still refer to the provisions stipulated in Law No. 2 of 2014 on the Position of Public Notary. In exercising its authority in providing legal counseling, notaries are required to have broad insights and views in order to be able to direct the contents of the deed in accordance with the provisions of the applicable legislations. The notary is expected to apply the precautionary principle in making the Deed to minimize errors in the making.